2017
DOI: 10.1080/14647273.2017.1322718
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of de novo DAZ microdeletion in sperm nuclei of subfertile men: possible involvement of genome instability in idiopathic male infertility

Abstract: The occurrence and diagnosis of Y-chromosome microdeletions, specifically deletions of the DAZ (Deleted in Azoospermia) genes are an important issue in male infertility. Screening Y chromosome microdeletion is mainly done using polymerase chain reaction (PCR) on blood leukocytes. However, there is some evidence indicating that presence of DAZ in somatic cells might not be indicative of its presence in the germ cell lineage. Therefore, a total of 130 men with poor semen quality were examined for presence of DAZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…However in the outmost side, the blood leukocytes AZFc deletion frequency in azoospermia patients is reported to be 10–15%. Although, recent report indicates that a high frequency of microdeletions in AZFc region especially DAZ gene might occur de novo during spermatogenesis when sperm nuclei are studied [8],[40]. Genome instability in azoospermia factor ( AZF ) region of Y chromosome especially in the DAZ genes was shown previously to occur in lymphocytes of men exposed to low dose and background level of ionizing radiation [31],[32] and in irradiated leukocytes in vitro [33].…”
Section: Discussionmentioning
confidence: 99%
“…However in the outmost side, the blood leukocytes AZFc deletion frequency in azoospermia patients is reported to be 10–15%. Although, recent report indicates that a high frequency of microdeletions in AZFc region especially DAZ gene might occur de novo during spermatogenesis when sperm nuclei are studied [8],[40]. Genome instability in azoospermia factor ( AZF ) region of Y chromosome especially in the DAZ genes was shown previously to occur in lymphocytes of men exposed to low dose and background level of ionizing radiation [31],[32] and in irradiated leukocytes in vitro [33].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that this observation might be a possible explanation for induction of azoospermia and oligozoospermia after radiotherapy ( 48 ). Further studies by Mozdarani and Ghoraeian using a combined FISH and PRINS technique for detection of DAZ microdeletion in individual sperms showed considerably higher frequency of DAZ microdeletion in sperms of subfertile individuals whom their leukocytes were normal for DAZ gene ( 49 - 51 ).…”
Section: Yq Microdeletionmentioning
confidence: 96%
“…These data indicate that IAS with a “clean karyotype background” is one of the leading causes of male infertility 3 . Therefore, subtle genetic defects in the somatic cells of IAS males with a clean karyotype background, which may be missed by G-banding screening, need to be further investigated 4 .…”
Section: Introductionmentioning
confidence: 99%